2018
DOI: 10.1021/acs.jpcc.8b03393
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Mechanisms of Strain-Dependent Thermal Conductivity of Polycrystalline Graphene with Varying Grain Sizes and Surface Hydrogenation

Abstract: In this paper, the thermal conductivities (κ) of polycrystalline graphene (PG) with varying average grain size are investigated using reverse nonequilibrium molecular dynamics method. Due to the presence of grain boundary (GB), the κ of PG is found to depend on the average grain size as well as in-plane strain and hydrogenation coverage. The principles and mechanisms for the change of κ with in-plane strain and surface hydrogenation are interpreted combining the thermal transport theory and phonon density of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…However, when the GB energy is high enough, κ is more sensitive to the grain size than the GB energy. 101 In addition, when grains and GBs are present in 2D materials, some modulation means, such as strain, 96 doping, 102 and tilt angle, 103 will also have different effects on its thermal transport properties than in the single crystal case.…”
Section: Intrinsic Structure Engineeringmentioning
confidence: 99%
“…However, when the GB energy is high enough, κ is more sensitive to the grain size than the GB energy. 101 In addition, when grains and GBs are present in 2D materials, some modulation means, such as strain, 96 doping, 102 and tilt angle, 103 will also have different effects on its thermal transport properties than in the single crystal case.…”
Section: Intrinsic Structure Engineeringmentioning
confidence: 99%
“…The interactions between carbon atoms are described by the adaptive intermolecular reactive empirical bond order (AIR-EBO) potential, 31 which has been widely used and conrmed in graphene-based material systems. [32][33][34] The original parameter of the carbon-carbon cutoff distance in the potential is modied to be 2.0 Å to avoid a known non-physical post-hardening phenomenon. 35,36 The timestep is set at 0.5 fs during the overall simulation.…”
Section: Calculations Of Mechanical Properties By Molecular Dynamics ...mentioning
confidence: 99%
“…These studies and related discoveries raised a series of questions for material physics research, and also provided opportunities for the preparation and design of micro–nano materials and structures. In 2018, A. R. Wei 85 used a reverse nonequilibrium molecular dynamics method to study the effect of the grain boundary and hydrogenation on the strain-dependent thermal conductivity of hydrogenated polycrystalline graphene under the condition of a strain field. The results showed that the thermal properties of hydrogenated polycrystalline graphene under tension load were related to the average stress in the hydrogenated polycrystalline graphene due to the softening of the phonon modes.…”
Section: Coupling Effect Of Defects In Multiple Physical Fieldsmentioning
confidence: 99%
“…The results showed that the thermal properties of hydrogenated polycrystalline graphene under tension load were related to the average stress in the hydrogenated polycrystalline graphene due to the softening of the phonon modes. 85 This could be attributed to the fact that both hydrogenation and oxidation will gradually change the material from a honeycomb to a diamond-like structure as result of the hybridization transition from sp 2 to sp 3 , while the introduction of grain boundary will only lead to the distortion of sp 2 hybridization. 86 Also in 2018, using molecular dynamics, the coupling effects of an external field (temperature and strain) and internal field (longitudinal and transverse defects) on the mechanical properties of Gr/h-BN–Cu heterostructures were investigated by L. Fan et al 87 As a result, atoms near the defect are more likely to escape covalent bond forces when the temperature increases.…”
Section: Coupling Effect Of Defects In Multiple Physical Fieldsmentioning
confidence: 99%